2008
DOI: 10.3858/emm.2008.40.1.98
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of proliferative and differentiation potentials of human embryonic stem cells during long-term culture

Abstract: Human embryonic stem cells (hESCs) are considered to be able to stably maintain their characteristics in vitro for prolonged periods, but we had previously encountered changes in proliferative ability and differentiation potential during extended culture of hESCs. Therefore, we investigated the proliferative ability and differentiation potential of hESCs during long-term culture. The hESCs, SNUhES3, were used to analyze population-doubling time, proliferation rate and differentiation potential. We classified h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 32 publications
3
26
0
Order By: Relevance
“…Immunocytochemistry was performed as described in previous report (Park et al, 2008). The cells were incubated with the following primary antibodies: rabbit anti-Oct 4 antibody (1:400; Santa Cruz Biotechnology, Inc., Santa Cruz, CA, http://www.scbt.com), mouse anti-Tra-1-60 (1:400; Chemicon, Temecula, CA, http://www.millipore.com), rabbit anti-brachyury ( …”
Section: Immunocytochemistrymentioning
confidence: 99%
“…Immunocytochemistry was performed as described in previous report (Park et al, 2008). The cells were incubated with the following primary antibodies: rabbit anti-Oct 4 antibody (1:400; Santa Cruz Biotechnology, Inc., Santa Cruz, CA, http://www.scbt.com), mouse anti-Tra-1-60 (1:400; Chemicon, Temecula, CA, http://www.millipore.com), rabbit anti-brachyury ( …”
Section: Immunocytochemistrymentioning
confidence: 99%
“…Both groups consistently reported an increased proliferation of ESCs at higher passages, no changes in telomerase activity as well as a reduced differentiation ability. However, while Park et al (2008) found no karyotypic changes Xie et al (2010) described some karyotypic abnormalities (translocation) in one of the two hES cell lines analysed while Maitra and co-workers (2005) and found karyotypic anomalies in 8 out of 9 analysed human ESC lines at high passage numbers. These included copy number changes (amplifications and deletions of chromosomes, 45%) and gene promoter methylation (90%).…”
Section: Long Term Cultivation and Karyotypic Stabilitymentioning
confidence: 90%
“…This might depend on the species (mouse or human) as well as the (often sub-optimal) culture conditions. Various groups had cultivated human embryonic stem cell lines for around 100 passages (Maitra et al, 2005, Park et al, 2008, Xie et al, 2010. Park et al (2008) and Xie et al (2010) did not find any gross morphological changes or different expression levels for stem cell markers between early and late passages.…”
Section: Long Term Cultivation and Karyotypic Stabilitymentioning
confidence: 98%
See 1 more Smart Citation
“…19,20 Thus, for a given cell line, when considering an equal inoculum concentration and an equal elapsed time in culture, it is expected that colonies with similar areas be formed.…”
Section: Morphologic Stability and Pluripotencymentioning
confidence: 99%